Non-Transmissible Measles Virus Vector Selectively Induces Human Primed and Naïve like Pluripotent Stem Cells from Hematopoietic Cells - Hiramoto, Takafumi; Tahara, Maino; Sakamoto, Chika; Ono, Hiroaki; Kohara, Hiroshi; Takeda, Makoto; Tani, Kenzaburo (Blood, 2015)
Our newly gene transfer vector could transduce multiple genes simultaneously into human hematopoietic cells with higher efficiency than general gene transfer vector. By using the vector, we could induce high quality pluripotent stem cells (naïve like pluripotent stem cells) from human cord blood derived CD34+ cells. Measles virus (MV) which belongs to negative single strand RNA viruses has been known to have high affinity for human immune cells including monocytes, B cells and T cells. Although MV induced severe diseases, most of MV induced diseases can be controlled and curable by effective vaccination against H glycoprotein. Based on this background, we have newly developed novel measles virus vector to achieve the efficient and safe gene transfer to various cells. Our MV gene transfer vector is non-transmissible and transfer multiple genes simultaneously into human cells. Exogenous gene expressions from MV vector were controlled by changing the position in the vector genome. The MV vector which encoded 5 genes (enhanced GFP, human OCT3/4, SOX2, KLF4, and L-MYC) (MV-ΔF-OSKL-EGFP) induced transgenes in almost all of hematopoietic cells besides natural killer cells. Quiescent T cells (CD45RA and CD197 expressed T cells), which include Naive and stem cell memory T cells were also transduced by MV-ΔF-OSKL-EGFP. For the purpose of transducing genes into hematopoietic cells safety and developing novel immunotherapy for cancer using gene modified T cells, our current results strongly suggested that the newly developed MV vector is considered to be more powerful vector than conventional gene transfer methods. Then, we generated induced pluripotent stem cells (primed iPS cells) from terminal differentiated T cells and naive like pluripotent stem cells (NL-iPS cells) from cord blood derived CD34+ cells using MV-ΔF-OSKL-EGFP in same culture method and culture media. These primed iPS and GSL-iPS cells were demonstrated to express pluripotent markers (OCT3/4, NANOG) and differentiate into three germ line tissues. NL-iPS cells also expressed TFE3 proteins in the nuclei and SSEA1 in the cytoplasm. Interestingly, Enhanced GFP from MV-ΔF-OSKL-EGFP were lost in primed iPS cells and expressed strongly in NL-iPS cells. In the case of establishing iPS cells using this MV vector from CD34+ cells, we could establish only NL-iPS cells but not primed iPS cells, whereas we could not establish NL-iPS cells by using conventional vectors including Sendai vious vector in the same methods as MV vector. In conclusion, our newly developed MV vector is considered to lead revolutionary advance in the research and clinical fields of gene therapy and stem cell. No relevant conflicts of interest to declare.